THE UNITED STATES–ISRAEL–IRAN CONFLICT AND GLOBAL BUSINESS: AN INTEGRATED ANALYSIS OF GEOPOLITICAL RISK, ENERGY SECURITY, AND SUPPLY CHAIN RESILIENCE (POLITEKNIK LP3I JAKARTA, 2026)
Geopolitical conflicts have become increasingly significant determinants of global business performance by generating uncertainty across energy markets, international trade, financial systems, and global supply chains. The recent escalation involving the United States, Israel, and Iran has intensified concerns regarding global economic stability due to its strategic implications for energy security and international commercial activities. Despite extensive research on the macroeconomic and financial consequences of geopolitical conflicts, limited attention has been devoted to understanding their integrated implications for multinational enterprises and global business operations. Therefore, this study aims to analyze the influence of the United States–Israel–Iran conflict on global business by integrating perspectives from geopolitical risk, energy security, and supply chain resilience. This study employs a descriptive qualitative research design using a systematic literature review approach. Secondary data were collected from peer-reviewed journal articles, academic publications, and reports from international organizations, which were analyzed through thematic content analysis. The findings indicate that the conflict influences global business through four interconnected transmission channels: geopolitical uncertainty, energy security disruption, global supply chain instability, and financial market volatility. These mechanisms increase production and transportation costs, weaken investor confidence, disrupt international trade, and encourage multinational corporations to adopt resilience-oriented strategies, including supplier diversification, regionalized production, and enhanced geopolitical risk management. This study contributes to the international business literature by developing an integrated analytical framework that explains how geopolitical conflict simultaneously affects business strategy, international investment, and supply chain resilience. The findings provide practical insights for policymakers and business leaders in strengthening organizational resilience and managing geopolitical risks within an increasingly uncertain global business environment.